ANALISIS RISIKO FAKTOR-FAKTOR NON EXCUSABLE PADA TAHAP PELAKSANAAN PROYEK PEMBANGUNAN PERUMAHAN DI KOTA MANADO - Andries, Lenny; Mandagi, R J; Willar, Debby (Sam Ratulangi University, 2017)
The delay caused by non-excusable factors leads to a change in performance that is entirely the responsibility of the contractor. The purpose of this study is to identify, analyze and develop risk response on the non-excusable dominant risk factors that affect the project performance. The target of the respondent is the contractor that have worked on the housing development project â€œXâ€ in the city of Manado.Â Â Â Â Â Â Â Â Â Â Â Â Â Â The results of the study were analyzed by using Analytic Hierarchy Process (AHP) method; the non-excusable factors which had the dominant risk to the project change were labor shortage, unreliable subcontractor, labor absenteeism, inefficient communications related to material ordering, and inappropriate scheduling implementation. The risk responses taken are appropriate planning, good communication and coordination, and supervision and control in every stage of the project implementation process.Â Keywords: Risk, Non Excusable, Analytic Hierarchy Process (AHP).